Study of Potential and Constraints in Developing Tua Tourism Village, Tabanan as a Leading Destination in Bali - I Nengah Wirata; I Putu Esa Widaharthana; Ratri Paramita; I Gede Sumadi; IGA. Ratih Asmarani (Eduvest - Journal of Universal Studies, 2025)
This research aims to explore the potential and challenges in developing Tua Tourism Village, Marga District, Tabanan Regency, as a sustainable tourism destination. The Tua Tourism Village has a unique attraction in the form of rich culture, traditions and natural potential that supports the development of community-based tourism. However, the management of this tourist village still faces a number of obstacles, such as limited infrastructure, low involvement of local communities, and lack of digital promotion. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews, observation and documentation, involving tourist village managers, local communities, local government and tourists as resource persons. The results of the study indicate that the sustainability of the development of the Tua Tourism Village requires synergy between managers, communities, and government, as well as more innovative promotional strategies. Recommendations provided include increasing human resource capacity, improving infrastructure, and optimizing digital technology-based marketing. This study is expected to provide practical contributions to the development of the Tua Tourism Village and other tourism villages in Bali.